A prospective randomised double-blind study of comparison of efficacy and safety of dexmedetomidine and clonidine as adjuvants to intrathecal isobaric ropivacaine 0.75% in lower limb surgeries - Kallapur, Basavaraj; H. S., Yashavanthi; Sheikh, Safiya I. (International Journal of Research in Medical Sciences, 2019)
Background: Studies comparing the efficacy of dexmedetomidine and clonidine as adjuvants to ropivacaine 0.75% in spinal anesthesia are few. The objective was to study the safety and efficacy of dexmedetomidine in comparison to clonidine as an adjuvant to ropivacaine in subarachnoid block. Methods: Patients were randomly allotted into 3 groups. Group R (n=30) patients received 3ml of 0.75% isobaric ropivacaine +0.5ml of 0.9% normal saline to a total volume of 3.5ml. Group RD (n=30) patients received 3ml of 0.75% isobaric ropivacaine +5μg of dexmedetomidine +0.9% normal saline to a total volume of 3.5ml. Group RC (n=30) patients received 3ml of 0.75% isobaric ropivacaine +30μg of clonidine +0.9% normal saline to a total volume of 3.5ml. The patients and the investigator were blinded for the study. Results: Time to reach T10 level of sensory block in group R was 7.6±1.3 min, group RC was 7.8±1.4 min and in group RD it was 7.9±1.4 min which was statistically not significant with p value 0.66. Time to reach motor onset to Bromage scale 4 was 9.8±1.4 min in group R, 10±1.4 min in group RC, 10.5±1.5 min in group RD which was statistically not significant with p value 0.24. Time to reach maximum sensory block in group R was 10.7±1.4 min, 10.6±1.1 min in group RC, 11±1.7 min in group RD which was statistically insignificant with p value 0.51. Conclusions: Intrathecal dexmedetomidine had superior anaesthetic effects with respect to duration of sensory blockade, motor blockade and duration of analgesia compared to intrathecal clonidine.